Potential concerns regarding the use of sex-specific cutpoints for high-sensitivity troponin assays: counterpoint - Giannitsis, Evangelos (Clinical chemistry, 2017)
There are biological differences between males and females in cardiac structure and function that have been recently revealed using sensitive imaging techniques such as magnetic resonance tomography (1). With the availability of more sensitive assays capable of measuring extremely low concentrations of cardiac troponin, such biological differences may contribute to 99th percentile reference values for cardiac troponin that have been found to be lower in women than in men (2). Although it is still unclear whether clinical evidence is strong enough to support the use of sex-specific cutoffs in clinical practice, the Joint ESC/ACCF/AHA/WHF (European Society of Cardiology/American College of Cardiology Foundation/American Heart Association/World Heart Federation) Task Force for the Universal Definition of Myocardial Infarction already recommends the use of sex-specific cutoffs (3). However, there are several reasons to question such a general recommendation including a lack of consistent clinical evidence, the need to validate such criteria for each high-sensitivity (hs)2 cardiac troponin assay owing to potential analytical differences between assays, and the wide variation in 99th percentile values across commercially available cardiac troponin assays (4). These issues may confuse clinicians and translate into the incorrect incorporation of such limits into clinical routine as diagnostic algorithms become increasingly complicated.In particular, there are 5 relevant concerns that argue against such a recommendation and that require more elaboration.1. Clinical evidence supporting the use of sex-specific cutoffs is sparse and controversial. Application of sex-specific 99th percentile values (4) was reported to increase numbers of non-ST elevation myocardial infarctions (NSTEMIs) by 4.7%-11% in females depending on the hs-cardiac troponin assay used, but also to decrease numbers of NSTEMIs in males by 2%-3% (5-7). Whether diagnostic reclassification translates into improved prediction of …